2009
DOI: 10.1002/ejoc.200900299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Quinone Methides: Reference Electrophiles for the Construction of Nucleophilicity Scales

Abstract: Keywords: Electrophilicity / Nucleophilicity / Kinetics / Linear free-energy relationships / Quinone methides Novel synthetic routes to the aryl-substituted quinone methides 3a-f have been developed, and a previously reported Mannich approach has been used for the syntheses of the acceptor substituted quinone methides 2e-g. The secondorder rate constants for the reactions of 3c-f and 2e-g with the carbanions 9a-h were determined photometrically in DMSO. With Equation (1), log k 2 = s (N + E), and the known nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 65 publications
1
68
0
1
Order By: Relevance
“…As can be seen, the electrophilic character of benzoselenadiazolium cation 1 of −14.72 can be compared with values of −14.36 for 2,6‐di‐tert.butyl‐4‐(4‐nitrobenzylidene)cyclohexa‐2,5‐dienone 5 , −14.70 for 4‐methoxy‐nitrostyrene 6 , and −14.91 for 1,2‐diaza‐1,3‐diene in DMSO 7 .…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, the electrophilic character of benzoselenadiazolium cation 1 of −14.72 can be compared with values of −14.36 for 2,6‐di‐tert.butyl‐4‐(4‐nitrobenzylidene)cyclohexa‐2,5‐dienone 5 , −14.70 for 4‐methoxy‐nitrostyrene 6 , and −14.91 for 1,2‐diaza‐1,3‐diene in DMSO 7 .…”
Section: Resultsmentioning
confidence: 99%
“…3 Consequently, the rate constants k Nu for addition of nucleophiles to a di-CF 3 substituted quinone methide (Scheme 3A) are correlated by the N + scale for nucleophile addition to strongly resonance stabilized carbocations, 4,5 and quinone methides have been used by Mayr, alongside other carbocations, as reference electrophiles in the construction of nucleophilicity scales. 6 The efficient and synthetically useful 2 + 4 addition of electron-rich alkenes to 1,2 quinone methides can be similarly understood as the stepwise electrophilic addition of a resonance stabilized benzylic carbocation to nucleophilic alkene, followed by capture of the oxocarbenium ion intermediate by phenoxide ion (Scheme 3B). 7 …”
Section: Introductionmentioning
confidence: 99%
“…Because the nucleophilic activities of amines are known to correlate only poorly with their Brønsted basicities (p K aH ),33–35 we now set out to include the tertiary amines 1(a–d) in our comprehensive nucleophilicity scales36–40 by studying the rates of their reactions with benzhydrylium ions 36 …”
Section: Introductionmentioning
confidence: 99%
“…Numerous kinetic investigations have shown that the rate constants for the reactions of n ‐, π ‐, and σ ‐nucleophiles with carbocations can be described by Eqn (1),36–40 where nucleophiles are characterized by two parameters ( N, s ) and electrophiles are characterized by one parameter ( E ). By employing benzhydrylium ions ( 2 , Table 1)36 and structurally related quinone methides40 as reference electrophiles, it became possible to compare reactivities of a large number of nucleophiles in a single scale 36–40. With this methodology, we have previously quantified the nucleophilicities of numerous n ‐, π ‐, and σ ‐nucleophiles,41 including primary and secondary amines,42 pyridines,43 amidines,44 cinchona alkaloids,45 as well as the tertiary alkylamines 1e,f 46.…”
Section: Introductionmentioning
confidence: 99%